Toward a holistic approach of evaluating higher education institutes - CHEN, Yidan (Institutional Knowledge at Singapore Management University, 2019)
In this thesis, I argue that higher education institutes generate significant positive externalities and other virtual benefits to the society they embedded in, which often dwarf the direct economic returns created. It would be an unfortunate oversimplification to throw economic theories developed from the private sector directly to higher education institutes without acknowledging their unique social values. Following a long tradition of integrating social and economic perspectives, I proposed a conceptual paradigm for higher education system to cover its social as well as economic role. An institute sets strategic intents to live up to stakeholders’ expectations and then develops an organizational structure to fulfill such intents. Unlike other organizations, a college/university has quite a diverse base of stakeholders and therefore multiple strategic intents. Those intents may conflict with one another from time to time. Evaluating a higher education institute therefore should count in all these social-economic intents. A holistic method of merit-evaluation will then be derived from this conceptual paradigm. I applied the proposed paradigm under a China context and found that the distribution of government’s supports is uneven with a consistent favor towards large comprehensive research universities. University ranking influenced how the public fund was allocated, and social impact measured by two sets of mobile internet-based data moderated such an influence. I concluded that although research universities are the shining stars in the higher education system, they are not the whole picture of the advanced and sophisticated examples such as American’s enviable university networks. Rather, the strength of such a system resides in both the celebrated faculties and high-quality graduates, and the diversity and inclusiveness of all kinds of schools and students. The support of star research universities should not be at the expenses of sagging small specialized teaching schools. Hopefully, by applying a new and more balanced evaluation method, these small specialized institutes would shine as did their large comprehensive peers.